Establishing the Connection between Project Governance and Poverty Alleviation - Latiff , Abdul Muhaimin Abdul; Jaapar, Aini (International Journal of Psychosocial Rehabilitation, 2020)
Poverty alleviation is an integrated and continuous efforts conducted to reduce and further eliminate incident of poverty in the country through many approaches including the execution of programmes and projects related to poverty alleviation. Project governance is identified as a management system which can be utilized to ensure the effectiveness and the attainment of poverty alleviation projects. While project governance could contribute to the effective delivery of poverty alleviation programmes and projects, it is crucial to investigate the relevant elements of project governance in the context of poverty alleviation programmes and how they are connected. This study was conducted with the aim to identify project governance elements that applicable to poverty alleviation hence, explore the connection between project governance and poverty alleviation which could be found in the literature. This paper focuses on papers from journal articles, international reports, related books and government documents. The keywords included “project governance”, “governance” and “poverty alleviation”. Literature materials were selected to reflect the purpose of the study from key words search in the online databases and reviewed to find the connection between these two research areas.From the literatures, several definitions, elements and issues of project governance and poverty alleviation in Malaysia were discovered. This paper identifies several elements which act as a bridge in connecting project governance and poverty alleviation including effective delivery system, decision making, transparency, accountability, stakeholder management, governance structure and trust.The combination of these project governance elements in the context of poverty alleviation programs will pave the way for the development of project governance frameworks which subsequently contribute to the successful execution of poverty alleviation projects as well as the achievement of projects outcomes.The connection of project governance and poverty alleviation was established and this could be a success factor for poverty alleviation initiatives.